2001
DOI: 10.1007/s11627-001-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of the medicinal plant Plumbago zeylanica L. Through nodal explants

Abstract: A protocol for rapid in vitro propagation using nodal explants obtained from 2-yr-old, field-grown medicinal plants of Plumbago zeylanica L. belonging to the family Plumbaginaceae is described. High frequency bud break and fast development of shoots were induced on Murashige and Skoog's basal medium supplemented with 27.2 mM adenine sulfate +2.46 mM indole-3-butyric acid (IBA). Induction of rooting was achieved by transferring the shoots to the same basal medium containing 4.92 mM IBA. Using our protocol from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
(12 reference statements)
3
10
2
Order By: Relevance
“…Sahoo and Debata (1998) reported that a rapid and highly effective method for plant micropropagation from vegetative shoot buds was established for this medicinal plant Plumbago zeylanica L. ; multiple shoots were proliferated from nodal explants culture on MS basal medium supplemented with 0.25-1.0 mg/l Kn or 0.25-1.0 mg/l BAP. A similar phenomenon was observed in Plumbago zeylanica L. by other researchers (Gbadamosi and Egunyomi, 2010;Mallikadevi et al, 2008;Selvakumar et al, 2001;Rout et al, 1999;Verma et al, 2002).…”
supporting
confidence: 85%
“…Sahoo and Debata (1998) reported that a rapid and highly effective method for plant micropropagation from vegetative shoot buds was established for this medicinal plant Plumbago zeylanica L. ; multiple shoots were proliferated from nodal explants culture on MS basal medium supplemented with 0.25-1.0 mg/l Kn or 0.25-1.0 mg/l BAP. A similar phenomenon was observed in Plumbago zeylanica L. by other researchers (Gbadamosi and Egunyomi, 2010;Mallikadevi et al, 2008;Selvakumar et al, 2001;Rout et al, 1999;Verma et al, 2002).…”
supporting
confidence: 85%
“…1d) when cultured individually on root induction medium consisted of halfstrength MS medium with 0.5 mg/l IAA (Table II). Use of auxins singly or in combination for rooting was also reported by different authors (Gbadamosi and Egunyomi, 2010;Mallikadevi et al, 2008;Hassan and Khatun, 2010;Selvakumar et al, 2001;Rout et al, 1999;Verma et al, 2002).…”
Section: Resultssupporting
confidence: 54%
“…In general, micropropagation through axillary shoot proliferation has proven to be a handy tool [11] An appreciable level of success has been achieved by many investigators in the case of many tropical medicinal plants through micropropagation as in case of Hemidesmus indicus ([12], Cleistanthus collinus [13], Gmelina arborea [14], Plumbago zeylanica [15] and Holarrhena antidysenterica [16]. Although there are techniques have been reported for in vitro propagation of Aegle marmelos from in vitro grown seedling parts, i.e.…”
Section: Introductionmentioning
confidence: 99%